If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45 + 18 = -4x + 13x Combine like terms: -45 + 18 = -27 -27 = -4x + 13x Combine like terms: -4x + 13x = 9x -27 = 9x Solving -27 = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -27 + -9x = 9x + -9x Combine like terms: 9x + -9x = 0 -27 + -9x = 0 Add '27' to each side of the equation. -27 + 27 + -9x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + -9x = 0 + 27 -9x = 0 + 27 Combine like terms: 0 + 27 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| 2(4-3.5y)=22.5 | | 7(x-35)=5x | | 15b^2+6b=4b+10b^2+14 | | 4x-2(x-2)=-4+5x-10 | | 24-6x=10+8x | | x-(-14)=-2 | | -0.004*4.2= | | -6(7x-5)=72 | | (4b^9)= | | x+log(x)=0 | | 8x+17-7x=-3-12 | | 3.6+(-0.6)= | | x+(-3)=-3 | | 3.6+(-6.5)= | | 55=x^2*3.14 | | 53y=13(4y+30) | | 28+24x=42+17m | | 45=x^2*3.14 | | 5k+3-3k=6k | | -6(3+7x)=-438 | | xy+y=x | | 7(35x)=5x | | 35=x^2*3.14 | | 3(3x-9)=9 | | 1.63-0.9= | | 9x+1=60+10x | | 19x+3=18x-16 | | 30=x^2*3.14 | | (x-p)=4 | | 6a+5b=12c | | 3(t+6)-16=-7 | | 39.30=6s+3.48 |